Structural and photoelectrochemical characterization of heterostructuredcarbon sheet/Ag MoO -SnS/Pt photocapacitor - Kajana, T.; Velauthapilla, D.; Shivatharsiny, Y.; Ravirajan, P.; Yuvapragasam, A.; Senthilnanthanan, M. (Elsevier, 2020)
Photocapacitors can harvest solar energy and store it in the form of electrical energy and are expected to solve theproblem of unstable power output of solar cells under fluctuating sunlight. In the present study, a novelheterostructured carbon sheet/Ag MoO -SnS/Pt photocapacitor was developed. In this photocapacitor, SnSnanoparticles act as capacitive platform via redox pseudocapacitance, whereas Ag MoO molecules act as the activecore of the photocapacitor. The crystalline structure and the surface morphology of Ag MoO -SnS film on carbonsheet was examined by powder X-ray diffraction method (XRD) and Scanning Electron Microscopy (SEM),respectively. The XRD pattern indicates that Ag MoO film on carbon sheet is in β phase with respect to Ag MoO .The SEM images reveal Ag MoO film on carbon sheet composing of cubic structures, and SnS film on carbonsheet/Ag MoO composing of spherical nanoparticles. The carbon sheet/Ag MoO -SnS/Pt heterostructuredphotocapacitor, when subjected to visible light illumination, showed a specific capacitance of 340 F/g with an opencircuit potential of 1.25 V vs. Ag/AgCl electrode. The high capacitance obtained with this novel device may be attributed to the large specific area and high conductivity of the Ag MoO -SnS film. This research study has openeda new avenue for an effective heterostructured photocapacitor
Keywords: Photocapacitor; Photoelectrochemical characterization; Specific capacitance; Silver molybdate; Carbon sheet